Purification of functional mouse skeletal muscle mitochondria using percoll density gradient centrifugation. - Anunciado-Koza, Rea Victoria P; Guntur, Anyonya R; Vary, Calvin P; Gartner, Carlos A; Nowak, Madeleine.; Koza, Robert A (Tufts University. Tisch Library., 2023)
Keywords: Percoll purification, Density gradient, Mitochondria, Bioenergetics, Skeletal muscle.; Springer Open.